Brazing aluminum alloy composite material and preparation method thereof
By applying modified anticorrosion coatings on the surface of aluminum alloy composite materials, the problem of insufficient corrosion resistance of aluminum alloy materials is solved, the corrosion resistance and mechanical properties of the material are improved, and the application range is expanded.
Patent Information
- Application Number
- CN202411408632.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-07
AI Technical Summary
The poor toughness, low hardness and poor wear resistance of aluminum alloy materials limit their wider application in the industrial field. Moreover, the corrosion resistance of traditional three-layer aluminum alloy composite materials is insufficient, making it difficult to meet the requirements of high-end customers.
By preparing an aluminum alloy composite material including a leather layer, a core layer and a leather layer, and applying a modified anticorrosion coating to its surface, the modified anticorrosion coating is made of epoxy resin, modified fly ash, dispersant, and diluted Made of agent, leveling agent and epoxy curing agent to improve the corrosion resistance of the material.
It improves the corrosion resistance and mechanical properties of aluminum alloy composite materials, expands its application range, and is simple in preparation and low in cost, suitable for industrial production.
Smart Images

Figure BDA0005077381790000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum alloy materials, and particularly relates to a brazing aluminum alloy composite material and a preparation method thereof. Background Art
[0002] Aluminum alloy is the most widely used type of nonferrous metal structural material in industry. Cast aluminum alloy has good casting properties and can be made into parts with complex shapes. It does not require large additional equipment and has the advantages of saving metal and reducing costs. At present, brazed aluminum alloy composite plates, strips, foils, etc. are widely used in automobile radiators, evaporators, condensers, oil coolers, rail transportation, air separation equipment and other fields.
[0003] However, due to the shortcomings of poor toughness, low hardness, and poor wear resistance of aluminum alloy, its wider application in the industrial field is limited. Although the production process of traditional three-layer aluminum alloy composite materials is relatively mature, its service life is limited due to its corrosion resistance. Even through alloying, only a thinner layer in the thickness direction can achieve layered corrosion. Although the corrosion resistance has been improved, it is still difficult to meet the requirements of high-end customers. Summary of the invention
[0004] In order to improve the corrosion resistance of a brazing aluminum alloy composite material, the present invention provides a brazing aluminum alloy composite material and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A first aspect of the present invention provides a method for preparing a brazed aluminum alloy composite material, comprising the following steps:
[0007] S1: adding fly ash and dopamine into a Tris-HCl buffer solution, stirring at room temperature, centrifuging, washing until the pH value of the upper solution is neutral, filtering, and drying to obtain modified fly ash;
[0008] S2: According to weight, epoxy resin, modified fly ash, dispersant and diluent are stirred and mixed, and leveling agent is added after mixing. After mixing, epoxy curing agent is added, and mixing is continued to be uniform to obtain anti-corrosion coating; since fly ash has poor dispersion performance and is prone to agglomeration, resulting in uneven mixing of anti-corrosion coating, polydopamine is used to modify the surface of fly ash, and the introduction of active surface modification layer improves the dispersibility and stability of fly ash, enhances the interfacial compatibility with epoxy resin, and effectively improves the comprehensive performance of anti-corrosion coating. The presence of corrosion-resistant mineral phases such as mullite in fly ash can improve the anti-corrosion ability of coating. The introduction of modified fly ash as filler and reinforcing agent improves the strength and barrier properties of the anti-corrosion layer and reduces the degradation of the coating under corrosive conditions. In addition, compared with other types of fillers, fly ash has the advantages of being cheap, easy to obtain, and environmentally friendly.
[0009] S3: preparing two skin material layers and a core material layer, and then milling both sides of the two skin material layers and the core material layer;
[0010] S4: stacking the skin material layer, the core material layer, and the skin material layer in order, hot rolling, cold rolling, intermediate annealing, and slitting to obtain a composite material;
[0011] S5: uniformly coating the coating obtained in S2 on the surface of the composite material obtained in S4, and drying the coating to obtain an aluminum alloy composite material.
[0012] Furthermore, the usage ratio of fly ash, dopamine and Tris-HCl buffer solution in S1 is 0.10-0.12 g: 0.10-0.12 g: 50 mL.
[0013] Furthermore, the weight ratio of epoxy resin, modified fly ash, dispersant, diluent, leveling agent and epoxy curing agent in S2 is 50-60:10-15:0.1-0.5:10-20:0.5-1:40-60.
[0014] Furthermore, the dispersant is at least one of benzyl alcohol and pyrogallol.
[0015] Furthermore, the leveling agent is at least one of leveling agent BYK300 and leveling agent BYK306.
[0016] Furthermore, the diluent is at least one of ethanol, n-butanol, xylene, ethyl acetate, butyl acetate, and distilled water.
[0017] Furthermore, the epoxy curing agent is at least one of polyamide, cardanol, and aromatic amine.
[0018] Furthermore, the intermediate annealing temperature is 360° C. to 390° C., and the holding time is 3 to 5 hours.
[0019] Furthermore, the composition and weight percentage of the skin material layer are: Si: 0.6-1.0%, Fe: 0.3-0.7%, Cu: 0.4-0.8%, Mn: 1.0-1.6%, Mg<0.10%, Zn<0.10%, Ti: 0.18-0.2%, Zr: 0.15-0.2%, the individual content of other elements is ≤0.05%, the total amount is ≤0.15%, and the balance is aluminum.
[0020] Furthermore, the components and weight percentages of the core material layer are: Si: 0.7-0.8%, Fe: 0.5-0.6%, Cu: 0.7-0.8%, Mn: 1.45-1.55%, Mg<0.03%, Zn<0.10%, Ti: 0.10-0.13%, Zr<0.05%, the individual content of other elements is ≤0.05%, the total amount is ≤0.15%, and the balance is aluminum.
[0021] A second aspect of the present invention provides a brazing aluminum alloy composite material prepared by the above steps.
[0022] Beneficial effects of the present invention:
[0023] The present application provides an aluminum alloy composite material, which includes a skin material layer, a core material layer and a skin material layer from top to bottom, to obtain a composite material, wherein various elements are added to the components of the skin material layer and the core material layer, so that the aluminum alloy composite material has excellent strength and toughness; finally, the surface of the obtained composite material is coated with an anti-corrosion coating to form a corrosion-resistant coating, so that the aluminum alloy composite material has high corrosion resistance and expands its application range. And its preparation method is simple and easy to operate, low cost, and suitable for industrial production.
[0024] The anticorrosive coating provided in the present invention is prepared from epoxy resin, modified fly ash, dispersant, diluent, leveling agent and epoxy curing agent, and has good mechanical properties, flexibility, water and salt spray resistance. It can be coated on the surface of aluminum alloy composite materials to improve its corrosion resistance, thereby expanding its application field. At the same time, the anticorrosive coating has a simple preparation process, good adhesion to aluminum alloy composites, good paint film flexibility, and excellent comprehensive performance, and has huge application potential and broad application prospects. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1
[0027] This embodiment provides a method for preparing a brazing aluminum alloy composite material, and the preparation steps are as follows:
[0028] S1: 0.10 g of fly ash and 0.10 g of dopamine were added to 50 mL of Tris-HCl buffer solution (pH = 8.5, 10 mM), stirred at room temperature for 6 h, centrifuged, washed with deionized water until the pH value of the upper solution was neutral, filtered, and dried to obtain modified fly ash;
[0029] S2: By weight, 50 parts of epoxy resin, 10 parts of modified fly ash, 0.3 parts of benzyl alcohol and 10 parts of ethanol were stirred and mixed, 0.5 parts of leveling agent BYK300 were added after mixing, and after mixing evenly, 50 parts of polyamide were added, and mixing was continued to obtain an anti-corrosion coating;
[0030] S3: preparing two skin material layers (the thickness of a single skin material layer is 50 mm) and a core material layer (the thickness is 350 mm), and then milling both sides of the two skin material layers and the core material layer;
[0031] Among them, the composition and weight percentage of the skin material layer are: Si: 0.65%, Fe: 0.4%, Cu: 0.5%, Mn: 1.2%, Mg: 0.08%, Zn: 0.07%, Ti: 0.2%, Zr: 0.2%, the individual content of other elements is ≤0.05%, the total amount is ≤0.15%, and the balance is aluminum.
[0032] The components and weight percentages of the core material layer are: Si: 0.72%, Fe: 0.52%, Cu: 0.7%, Mn: 1.45%, Mg: 0.02%, Zn: 0.08%, Ti: 0.10%, Zr: 0.04%, the individual content of other elements is ≤0.05%, the total content is ≤0.15%, and the balance is aluminum.
[0033] S4: stacking the skin material layer, the core material layer, and the skin material layer in order, hot rolling to obtain a hot-rolled coil with a thickness of 6 mm, cold rolling to obtain a cold-rolled coil with a thickness of 0.6 mm, intermediate annealing at a temperature of 370° C. for a holding time of 3 h, and slitting to obtain a composite material;
[0034] S5: uniformly coating the coating obtained in S2 on the surface of the composite material obtained in S4, and drying the coating to obtain an aluminum alloy composite material.
[0035] The brazing aluminum alloy composite material is prepared by the above steps.
[0036] Example 2
[0037] Compared with Example 1, the only difference is:
[0038] S1: 0.10 g of fly ash and 0.12 g of dopamine were added to 50 mL of Tris-HCl buffer solution (pH=8.5, 10 mM), stirred at room temperature for 6 h, centrifuged, washed with deionized water until the pH value of the upper solution was neutral, filtered, and dried to obtain modified fly ash.
[0039] Example 3
[0040] Compared with Example 1, the only difference is:
[0041] S2: By weight, 55 parts of epoxy resin, 15 parts of modified fly ash, 0.3 parts of benzyl alcohol and 10 parts of ethanol are stirred and mixed, 0.5 parts of leveling agent BYK300 are added after mixing, and after mixing evenly, 50 parts of polyamide are added and mixed evenly to obtain an anti-corrosion coating.
[0042] Comparative Example 4
[0043] Compared with Example 1, the only difference is:
[0044] S2: By weight, 60 parts of epoxy resin, 15 parts of modified fly ash, 0.3 parts of pyrogallol and 10 parts of xylene are stirred and mixed, and 0.8 parts of leveling agent BYK300 are added after mixing. After mixing evenly, 60 parts of cardanol are added and the mixture is continued to be mixed evenly to obtain an anti-corrosion coating.
[0045] Example 5
[0046] Compared with Example 1, the only difference is:
[0047] Among them, the composition and weight percentage of the skin material layer are: Si: 0.95%, Fe: 0.6%, Cu: 0.5%, Mn: 1.4%, Mg: 0.08%, Zn: 0.05%, Ti: 0.2%, Zr: 0.2%, the individual content of other elements is ≤0.05%, the total amount is ≤0.15%, and the balance is aluminum.
[0048] Example 6
[0049] Compared with Example 1, the only difference is:
[0050] The components and weight percentages of the core material layer are: Si: 0.78%, Fe: 0.52%, Cu: 0.75%, Mn: 1.50%, Mg: 0.02%, Zn: 0.08%, Ti: 0.10%, Zr: 0.02%, the individual content of other elements is ≤0.05%, the total amount is ≤0.15%, and the balance is aluminum.
[0051] Comparative Example 1
[0052] This comparative example provides a method for preparing a brazing aluminum alloy composite material, and the preparation steps are as follows:
[0053] S1: preparing two skin material layers (the thickness of a single skin material layer is 50 mm) and a core material layer (the thickness is 350 mm), and then milling both sides of the two skin material layers and the core material layer;
[0054] Among them, the composition and weight percentage of the skin material layer are: Si: 0.65%, Fe: 0.4%, Cu: 0.5%, Mn: 1.2%, Mg: 0.08%, Zn: 0.07%, Ti: 0.2%, Zr: 0.2%, the individual content of other elements is ≤0.05%, the total amount is ≤0.15%, and the balance is aluminum.
[0055] The components and weight percentages of the core material layer are: Si: 0.72%, Fe: 0.52%, Cu: 0.7%, Mn: 1.45%, Mg: 0.02%, Zn: 0.08%, Ti: 0.10%, Zr: 0.04%, the individual content of other elements is ≤0.05%, the total content is ≤0.15%, and the balance is aluminum.
[0056] S2: stacking the skin material layer, the core material layer, and the skin material layer in order, hot rolling to obtain a hot-rolled coil with a thickness of 6 mm, cold rolling to obtain a cold-rolled coil with a thickness of 0.6 mm, intermediate annealing at an intermediate annealing temperature of 370° C. for a heat preservation time of 3 h, and slitting to obtain an aluminum alloy composite material.
[0057] The brazing aluminum alloy composite material is prepared by the above steps.
[0058] Comparative Example 2
[0059] This comparative example provides a method for preparing a brazing aluminum alloy composite material, and the preparation steps are as follows:
[0060] S1: By weight, 50 parts of epoxy resin, 10 parts of fly ash, 0.3 parts of benzyl alcohol and 10 parts of ethanol were stirred and mixed, 0.5 parts of leveling agent BYK300 were added after mixing, and after mixing evenly, 50 parts of polyamide were added, and the mixture was continued to be evenly mixed to obtain an anti-corrosion coating;
[0061] S2: preparing two skin material layers (the thickness of a single skin material layer is 50 mm) and a core material layer (the thickness is 350 mm), and then milling both sides of the two skin material layers and the core material layer;
[0062] Among them, the composition and weight percentage of the skin material layer are: Si: 0.65%, Fe: 0.4%, Cu: 0.5%, Mn: 1.2%, Mg: 0.08%, Zn: 0.07%, Ti: 0.2%, Zr: 0.2%, the individual content of other elements is ≤0.05%, the total amount is ≤0.15%, and the balance is aluminum.
[0063] The components and weight percentages of the core material layer are: Si: 0.72%, Fe: 0.52%, Cu: 0.7%, Mn: 1.45%, Mg: 0.02%, Zn: 0.08%, Ti: 0.10%, Zr: 0.04%, the individual content of other elements is ≤0.05%, the total content is ≤0.15%, and the balance is aluminum.
[0064] S3: stacking the skin material layer, the core material layer, and the skin material layer in order, hot rolling to obtain a hot-rolled coil with a thickness of 6 mm, cold rolling to obtain a cold-rolled coil with a thickness of 0.6 mm, intermediate annealing at a temperature of 370° C. for a holding time of 3 h, and slitting to obtain a composite material;
[0065] S4: The coating obtained in S2 is uniformly coated on the surface of the composite material obtained in S4, and dried to obtain an aluminum alloy composite material.
[0066] The brazing aluminum alloy composite material is prepared by the above steps.
[0067] Comparative Example 3
[0068] Compared with Example 1, the only difference is:
[0069] S2: By weight, 40 parts of epoxy resin, 7 parts of modified fly ash, 0.3 parts of benzyl alcohol and 10 parts of ethanol are stirred and mixed, 0.5 parts of leveling agent BYK300 are added after mixing, and after mixing evenly, 50 parts of polyamide are added and mixed evenly to obtain an anti-corrosion coating.
[0070] Comparative Example 4
[0071] Compared with Example 1, the only difference is:
[0072] The components and weight percentages of the skin material layer are: Si: 0.55%, Fe: 0.2%, Cu: 0.9%, Mn: 0.8%, Mg: 0.08%, Zn: 0.07%, Ti: 0.2%, Zr: 0.2%, the individual content of other elements is ≤0.05%, the total amount is ≤0.15%, and the balance is aluminum.
[0073] Comparative Example 5
[0074] Compared with Example 1, the only difference is:
[0075] The components and weight percentages of the core material layer are: Si: 0.72%, Fe: 0.40%, Cu: 0.6%, Mn: 1.45%, Mg: 0.05%, Zn: 0.15%, Ti: 0.10%, Zr: 0.04%, the individual content of other elements is ≤0.05%, the total content is ≤0.15%, and the balance is aluminum.
[0076] Performance tests were conducted on Examples 1 to 6 and Comparative Examples 1 to 5: (1) The tensile strength, yield strength and elongation of the obtained aluminum alloy composite material were tested in accordance with the standard GB / T228.1-2010 Metal Material Tensile Test Part 1: Room Temperature Test Method. (2) Corrosion resistance test: The obtained aluminum alloy composite material was placed in an internal corrosion durability test aqueous solution (22.4 mg NaCl, 8.9 mg Na2SO4, 0.27 mg CuCl2·2H2O, 14.5 mg FeCl3·6H2O, 1 L H2O) and circulated under the following conditions: In the first stage, the aqueous solution containing the sample was heated to 88°C within 0.5 h and maintained for 7.5 h. During the entire stage, the solution was stirred at a speed of 300 rpm; in the second stage, the solution was allowed to stand at room temperature for 16 h; and then the above two stages were repeated. The above two stages took 24 h to complete, and were repeated once for 1 day, for a total of 30 days. The test results are shown in Table 1:
[0077] Table 1
[0078]
[0079] It can be seen from the data in Table 1 that the tensile strength, yield strength and elongation in Examples 1-6 are higher than those in Comparative Examples 1-5, and the corrosion rate in Examples 1-6 is lower than that in Comparative Examples 1-5. It can be seen that the brazing aluminum alloy composite material provided by the present invention has good mechanical strength and corrosion resistance and has broad application prospects.
[0080] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0081] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a brazing aluminum alloy composite material, characterized in that: The following steps are involved: S1: adding fly ash and dopamine into a Tris-HCl buffer solution, stirring at room temperature, centrifuging, washing until the pH value of the upper solution is neutral, filtering, and drying to obtain modified fly ash; S2: According to parts by weight, epoxy resin, modified fly ash, dispersant and diluent are stirred and mixed, and after mixing, a leveling agent is added, and after mixing, an epoxy curing agent is added, and mixing is continued to obtain an anti-corrosion coating; S3: preparing two skin material layers and a core material layer, and then milling both sides of the two skin material layers and the core material layer; S4: stacking the skin material layer, the core material layer, and the skin material layer in order, hot rolling, cold rolling, intermediate annealing, and slitting to obtain a composite material; S5: uniformly coating the coating obtained in S2 on the surface of the composite material obtained in S4, and drying the coating to obtain an aluminum alloy composite material.
2. The method for preparing a brazing aluminum alloy composite material according to claim 1, characterized in that: The usage ratio of fly ash, dopamine and Tris-HCl buffer solution in S1 is 0.10-0.12 g: 0.10-0.12 g: 50 mL.
3. The method for preparing a brazing aluminum alloy composite material according to claim 1, characterized in that: The weight ratio of epoxy resin, modified fly ash, dispersant, diluent, leveling agent and epoxy curing agent in S2 is 50-60:10-15:0.1-0.5:10-20:0.5-1:40-60.
4. The method for preparing a brazing aluminum alloy composite material according to claim 1, characterized in that: The dispersant is at least one of benzyl alcohol and pyrogallol.
5. The method for preparing a brazing aluminum alloy composite material according to claim 1, characterized in that: The leveling agent is at least one of leveling agent BYK300 and leveling agent BYK306.
6. The method for preparing a brazing aluminum alloy composite material according to claim 1, characterized in that: The diluent is at least one of ethanol, n-butanol, xylene, ethyl acetate, butyl acetate, and distilled water; The epoxy curing agent is at least one of polyamide, cardanol and aromatic amine.
7. The method for preparing a brazing aluminum alloy composite material according to claim 1, characterized in that: The intermediate annealing temperature is 360°C ~ 390°C, and the holding time is 3 ~ 5h.
8. The method for preparing a brazing aluminum alloy composite material according to claim 1, characterized in that: The components and weight percentages of the skin material layer are: Si: 0.6-1.0%, Fe: 0.3-0.7%, Cu: 0.4-0.8%, Mn: 1.0-1.6%, Mg<0.10%, Zn<0.10%, Ti: 0.18-0.2%, Zr: 0.15-0.2%, the individual content of other elements is ≤0.05%, the total amount is ≤0.15%, and the balance is aluminum.
9. The method for preparing a brazing aluminum alloy composite material according to claim 1, characterized in that: The components and weight percentages of the core material layer are: Si: 0.7-0.8%, Fe: 0.5-0.6%, Cu: 0.7-0.8%, Mn: 1.45-1.55%, Mg<0.03%, Zn<0.10%, Ti: 0.10-0.13%, Zr<0.05%, the individual content of other elements is ≤0.05%, the total content is ≤0.15%, and the balance is aluminum.
10. A brazing aluminum alloy composite material, characterized in that: The invention is prepared by the preparation process described in any one of claims 1 to 9.